Metabolic syndrome and gingival inflammation in Caucasian children with a family history of obesity. (26th August 2013) - Kâ, Khady; Rousseau, Marie‐Claude; Lambert, Marie; Tremblay, Angelo; Tran, Simon D.; Henderson, Mélanie; Nicolau, Belinda
Abstract Aim To investigate whether metabolic syndrome (MetS) and its components are associated with gingival inflammation in children. Materials and Methods This is a cross‐sectional analysis from the baseline visit of the QUebec Adipose and Lifestyle InvesTigation in Youth cohort, an ongoing longitudinal study investigating the natural history of obesity in children of Quebec, Canada. The analytic sample includes 448 children aged 8–10 years, 39% of whom were overweight or obese. MetS was defined according to the International Diabetes Federation recommendations. Gingival inflammation was defined by the level of gingival crevicular fluid (GCF) tumour necrosis factor alpha (TNF‐α) and the extent of gingival bleeding. Sex‐specific linear regression analyses estimated the associations between MetS and gingival inflammation, adjusting for potential confounders. Results Twenty‐five children had MetS. Boys with MetS compared to those without, had a 49.5% (p‐value = 0.001) higher GCF TNF‐α level and 13.7% (p‐value = 0.033) more sites with gingival bleeding. Moreover, for three of the five components of MetS – waist circumference, fasting plasma triglycerides, systolic blood pressure – an increase was associated with increased GCF TNF‐α level in boys. No such findings were seen in girls. Conclusion An association between MetS and gingival inflammation was observed as early as in childhood, and may differ by sex.